Word Order and the First Person Singular in Portuguese and English - Maia, Belinda (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractFrom the perspective of contrastive linguistics, this article analyses the frequency and nature of the SVO sentence structure in English and Portuguese, particularly in those cases where the subject is realised by the first person pronoun I and eu respectively or by a name.